Strategi Program Banyuasin Religius Dalam Menciptakan Hafidz Qur’An di Rumah Tahfidz Hidayatullah Banyuasin III - Reira Havizha (CV. Ulil Albab Corp, 2023)
The background of this research is the Tahfidz Hidayatullah House Strategy which is quite interesting to study, because as a place it is not only a place for memorizing the Qur'an, but from 40 Tahfid Houses spread across Banyuasin, the students are recorded and the best are from villages and sub-districts, then they will be fostered here. after that it will be sent to competitions such as Musabaqoh Tilawatil Qur'an (MTQ). The research method used is through descriptive qualitative methods. With primary data sources from welfare and tahfidz teachers. With data collection techniques through observation, interviews and documentation. The results of the research show the program's strategy Religious Banyuasin itself aims to build a Tahfidz house for every village or sub-district, to form a religious village in every sub-district within the Banyuasin Regency, South Sumatra, and to cultivate and print memorizers of the Al-Qur'an. And one of them is the Tahfidz Al-Qur' House. an Hidayatullah Banyuasin III is also a place to recruit students who have good memorization, and the Tahfidz House is good enough, that can be seen from the strategy applied in memorizing the Qur'an for students in order to achieve the target of memorization. The strategy is also very close to achieving a goal. Tahfidz Al-Qur'an House Hidayatullah Banyuasin III in memorizing the Al-Qur'an uses muroja'ah strategies and methods, not switching to the verse being memorized.